Istidraj menurut Pemahaman Mufasir - Furqan Furqan; Diana Nabilah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
There are promises of Allah swt. in the Qur`an, such as promising of a way out from every problem and providing sustenance from unexpected directions for pious servants and providing a good life for those who believe and do good deeds. Instead, it will bring misery and torment to the disobedient. The fact is, not all faithful servants live in comfort and peace. Similarly with the sinful servant, which also not all live in misery as promised by Allah swt. This is because the consequences of immoral acts are sometimes postponed by Allah swt., the postponement of the punishment is called istidrāj. Mufasirs have two understandings regarding the meaning of istidrāj. First, istidrāj is interpreted as a postponement of punishment and only occurs in the hereafter. Second, istidrāj is the giving of some punishment while in this world and others in the hereafter. Ada beberapa janji Allah swt. dalam al-Qur`an, seperti menjanjikan jalan keluar pada setiap masalah dan memberikan rezeki dari arah yang tidak disangka-sangka bagi hamba bertakwa dan memberikan kehidupan yang baik bagi yang beriman dan beramal salih. Sebaliknya, akan memberikan kesengsaraan dan siksaan bagi mereka yang tidak taat. Kenyataannya, tidak semua hamba yang beriman hidup dalam kesenangan dan aman. Begitu juga dengan hamba yang bermaksiat, tidak semua hidup dalam kesengsaraan sebagaimana yang telah dijanjikan Allah Swt. Hal ini disebabkan bahwa konsenkuensi dari perbuatan maksiat terkadang ditangguhkan oleh Allah Swt, penangguhan azab tersebut diistilahkan dengan istidrāj. Para mufasir memiliki dua pemahaman terkait pemaknaan istidrāj. Pertama, istidrāj dimaknai sebagai penangguhan azab dan hanya terjadi di akhirat. Kedua, istidrāj adalah pemberian sebagian azab ketika di dunia dan sebagian lain di akhirat.